2015
DOI: 10.1002/pon.3802
|View full text |Cite
|
Sign up to set email alerts
|

The effect of expressive writing intervention on psychological and physical health outcomes in cancer patients—a systematic review and meta‐analysis

Abstract: Objective: This study aimed to evaluate the effectiveness of expressive writing intervention (EWI) for improving psychological and physical health in cancer patients and survivors.Methods: We searched databases and existing reviews for randomized controlled studies published between 1986 and 2014 that evaluated the effects of EWI on psychological and physical health outcomes. We computed and combined effect sizes and examined the role of methodological characteristics.Results: From 223 unique citations, we ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
45
0
5

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(53 citation statements)
references
References 65 publications
(105 reference statements)
3
45
0
5
Order By: Relevance
“…In this respect, the literature does not enable clearer conclusions. Contradictory results have been found on the repercussions of emotional expressiveness in psychological adjustment in women with cancer (Stanton et al, 2000;Stanton & Low, 2012;Zacharie & O´Toole, 2015), so the effect of emotional expression on well-being may be very dependent on context, especially the quality of the relationship it takes place in.…”
Section: Discussionmentioning
confidence: 93%
“…In this respect, the literature does not enable clearer conclusions. Contradictory results have been found on the repercussions of emotional expressiveness in psychological adjustment in women with cancer (Stanton et al, 2000;Stanton & Low, 2012;Zacharie & O´Toole, 2015), so the effect of emotional expression on well-being may be very dependent on context, especially the quality of the relationship it takes place in.…”
Section: Discussionmentioning
confidence: 93%
“…Dreizehn Übersichtsarbeiten behandelten unterschiedliche Tumorgruppen [10,11,12,13,14,15,16,17,18,19,20,21,22], in 7 ging es speziell um Brustkrebs [8,9,23,24,25,26,27] und in einer um Prostatakrebs [28]. …”
Section: Ergebnisseunclassified
“…Ein Review verglich multidimensionale mit monodimensionalen Interventionen [18] und eines untersuchte multidisziplinäre Rehabilitationsmodelle [8]. Ein Review schließlich befasste sich mit den Effekten von expressivem Schreiben [22]. Dauer und Häufigkeit der Interventionen unterschieden sich stark und reichten von einer einzelnen 20-minütigen Einheit [17] bis zu 60 wöchentlichen Einheiten [10].…”
Section: Ergebnisseunclassified
See 1 more Smart Citation
“…Despite the demonstrated benefits from those studies, a recent meta-analysis reviewed 16 randomized controlled trials and concluded no overall evidence for benefits of writing in psychological, physical, or quality of life outcomes [14]. Conversely, the review did suggest that those who experience low levels of emotional support may benefit from expressive writing.…”
mentioning
confidence: 99%